Binding Power of Minister of Manpower Regulation Number 16 of 2024 as a Basis for Determining Regency/ City Minimum Wages in 2025 - Soemali (Formosa Journal of Sustainable Research, 2024)
The existence of the Minister of Manpower Regulation Number 16 of 2024 as a legal basis has binding legal force because of its authority to fill the legal vacuum in determining the minimum wage in 2025